Water-based high transmittance anti-reflection coating solution for photovoltaic glass

By preparing water-based high-transmittance anti-reflective coating solution, the modified emulsion and porous puncture structure are used to improve the transmittance and environmental protection of photovoltaic glass, and the problems of insufficient light transmittance of photovoltaic glass and poor environmental protection of coating solution are solved, and the problems of insufficient light transmittance of photovoltaic glass and poor environmental protection of coating solution are improved. The efficiency of solar cells.

CN118791236BActive Publication Date: 2025-01-07SHANGHAI DAQIAOKANG NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411269274.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-07
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

At this stage, the light transmittance of photovoltaic glass is insufficient, resulting in low photoelectric conversion efficiency of solar cells and poor environmental protection of existing coating liquids.

Method used

The modified emulsion is prepared by reacting raw materials such as acrylic acid, 2-perfluorooctylethanol, p-methylbenzenesulfonic acid, and hexagonal boron nitride, sodium hydroxide, and 2- Modified fillers are prepared by materials such as aminoterephthalic acid to form a porous puncture structure, reducing light reflection and improving light transmittance.

Benefits of technology

It improves the light transmittance and anti-reflection effect of photovoltaic glass, enhances the environmental protection of the coating liquid, improves the output power of solar cells, and reduces the overall reflectivity of photovoltaic glass.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an aqueous high-transmittance anti-reflection coating liquid for photovoltaic glass. The aqueous high-transmittance anti-reflection coating liquid comprises the following raw materials in parts by weight: 40-50 parts of a modified emulsion, 5-8 parts of a modified filler, 1-2 parts of sodium dodecylbenzene sulfonate and 20-30 parts of deionized water. The main molecule of the modified emulsion in the coating liquid is polyacrylate, and the molecular side chain contains a long fluorocarbon chain. The fluorocarbon has a high refractive index and can reduce the reflection of light, thereby improving the transmittance. At the same time, sodium borohydride treatment can be used to transform the titanium dioxide sol on the surface into a spike shape. Finally, a calcination treatment is performed to carbonize the aluminum organic framework and decompose hexadecyltrimethylammonium bromide, so that the modified filler forms a porous structure, which cooperates with the spike-shaped titanium dioxide on the surface to form a porous thorn ball. During light irradiation, the incident light rays can be reflected multiple times in the porous thorn structure of the modified filler, and then consumed and absorbed, thereby reducing the overall reflectivity of the photovoltaic glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic glass coating liquid preparation, and in particular to an aqueous high-transmittance anti-reflection coating liquid for photovoltaic glass. Background Art

[0002] Solar cells, also known as photovoltaic cells, are semiconductor devices that convert sunlight directly into electrical energy. As they are green and environmentally friendly products that do not cause environmental pollution and are renewable resources, solar cells are an energy source with broad development prospects in today's energy shortage. The solar cell module packaging structure consists of photovoltaic glass, adhesive film, battery cells and back film. Sunlight needs to pass through photovoltaic glass to perform light-to-electricity conversion. However, with the current glass preparation process, the light transmittance of photovoltaic glass can only reach about 90%, and 10% of sunlight is still lost, thereby reducing the photoelectric conversion efficiency of solar cells. At present, by coating a layer of coating on the surface of photovoltaic glass, the light transmittance can be increased, thereby increasing the output power of solar cells. Summary of the invention

[0003] The purpose of the present invention is to provide an aqueous high-transmittance anti-reflection coating solution for photovoltaic glass, which solves the environmental protection problem of the coating solution used for photovoltaic cells at this stage, and at the same time improves the transmittance and anti-reflection effect.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A water-based high-transmittance anti-reflection coating solution for photovoltaic glass is prepared by the following steps:

[0006] Step A1: acrylic acid, 2-perfluorooctylethanol, p-toluenesulfonic acid and toluene are uniformly mixed, and reacted at a speed of 120-150 r / min and a temperature of 110-120° C. for 5-7 hours to obtain intermediate 1;

[0007] Step A2: Methyl methacrylate, butyl acrylate, acrylic acid, intermediate 1 and deionized water are uniformly mixed, and ammonium persulfate is added under stirring at a speed of 150-200 r / min and a temperature of 82-84° C. to react for 2-3 hours to obtain a modified emulsion;

[0008] Step A3: Weigh the following raw materials in parts by weight: 40-50 parts of modified emulsion, 5-8 parts of modified filler, 1-2 parts of sodium dodecylbenzene sulfonate and 20-30 parts of deionized water, mix the raw materials evenly, and prepare an aqueous high-transmittance anti-reflection coating liquid for photovoltaic glass.

[0009] Furthermore, the molar ratio of acrylic acid to 2-perfluorooctylethanol in step A1 is 1:1, and the amount of p-toluenesulfonic acid is 1% of the sum of the mass of acrylic acid and 2-perfluorooctylethanol.

[0010] Furthermore, the usage ratio of methyl methacrylate, butyl acrylate, acrylic acid, intermediate 1, deionized water and ammonium persulfate described in step A2 is 95g:73g:54g:35g:150mL:1.58g.

[0011] Further, the modified filler is prepared by the following steps:

[0012] Step B1: uniformly mix hexagonal boron nitride and sodium hydroxide solution, perform ultrasonic treatment for 1-1.5h at a frequency of 30-50kHz, heat to 120-125°C, reflux for 20-25h, filter to remove the filtrate, wash the substrate with dilute hydrochloric acid until neutral, and obtain hydroxylated hexagonal boron nitride; mix hydroxylated hexagonal boron nitride, 3-isocyanate propyltriethoxysilane and toluene, and react for 2-3h at a speed of 150-200r / min and a temperature of 25-30°C to obtain modified hexagonal boron nitride;

[0013] Step B2: 2-aminoterephthalic acid, aluminum chloride hexahydrate, DMF and deionized water are mixed, stirred at a speed of 500-600 r / min and a temperature of 20-25° C., citric acid is added, stirred for 10-15 minutes, heated to 150-160° C., and heat-treated for 20-25 hours to obtain an aluminum organic framework, and the aluminum organic framework, 3-isocyanate propyltriethoxysilane and toluene are mixed, and reacted at a speed of 150-200 r / min and a temperature of 25-30° C. for 2-3 hours to obtain a functionalized aluminum organic framework;

[0014] Step B3: uniformly mix the modified hexagonal boron nitride, the functionalized aluminum organic framework, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate and ethanol, perform ultrasonic treatment at a frequency of 20-30 kHz and a temperature of 40-50° C., add deionized water, perform ultrasonic treatment for 1-1.5 hours, and obtain a composite sol; disperse the composite sol in ethanol, add tetrabutyl titanate, stir and add deionized water at a speed of 200-300 r / min and a temperature of 25-30° C., raise the temperature to 90-95° C., and react for 1-1.5 hours to obtain a modified sol;

[0015] Step B4: Disperse the modified sol in deionized water, add polyvinyl pyrrolidone and sodium borohydride, react at a speed of 150-200 r / min and a temperature of 60-70°C for 30-35 hours, remove the supernatant by centrifugation, repeat step B4 for three times, place the substrate in a muffle furnace, and calcine for 5-7 hours at a temperature of 550-600°C in a nitrogen atmosphere to obtain a modified filler.

[0016] Further, the dosage ratio of hexagonal boron nitride and sodium hydroxide solution in step B1 is 1g:100mL, the concentration of sodium hydroxide solution is 5mmol / L, and the dosage of 3-isocyanatepropyltriethoxysilane is 3% of the mass of hydroxylated hexagonal boron nitride.

[0017] Furthermore, the dosage ratio of 2-aminoterephthalic acid, aluminum chloride hexahydrate, DMF, deionized water and citric acid in step B2 is 10mmol:10mmol:15mL:6mL:10mmol, and the molar ratio of amino group on the aluminum organic framework and 3-isocyanatepropyltriethoxysilane is 1:1.

[0018] Furthermore, the amount ratio of the modified hexagonal boron nitride, functionalized aluminum organic framework, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, ethanol and deionized water described in step B3 is 1g:1.5g:0.6:2.5g:20mL:3mL, and the amount ratio of the composite sol, ethanol, tetrabutyl titanate and deionized water is 1g:1mL:5μL:9μL.

[0019] Furthermore, the modified sol, deionized water, polyvinyl pyrrolidone and sodium borohydride in step B4 are used in a ratio of 5 g:10 mL:0.15 g:1 mg, and the model of polyvinyl pyrrolidone is K30.

[0020] Beneficial effects of the present invention: The present invention discloses an aqueous high-transmittance anti-reflection coating liquid for photovoltaic glass, which comprises the following raw materials: a modified emulsion, a modified filler, sodium dodecylbenzene sulfonate and deionized water. The modified emulsion uses acrylic acid and 2-perfluorooctylethanol as raw materials, so that the carboxyl group on the acrylic acid and the hydroxyl group on the 2-perfluorooctylethanol are esterified to obtain an intermediate 1. Methyl methacrylate, butyl acrylate, acrylic acid and the intermediate 1 are blended and polymerized to obtain the modified emulsion.

[0021] The modified filler is prepared by treating hexagonal boron nitride as a raw material with sodium hydroxide to obtain hydroxylated hexagonal boron nitride, treating the hydroxylated hexagonal boron nitride with 3-isocyanate propyl triethoxysilane so that the hydroxyl group on the hydroxylated hexagonal boron nitride reacts with the isocyanate group on the 3-isocyanate propyl triethoxysilane to obtain modified hexagonal boron nitride, coordinating 2-aminoterephthalic acid with aluminum trichloride hexahydrate to obtain an aluminum organic framework, and coordinating the aluminum organic framework with 3-isocyanate propyl triethoxysilane to obtain a modified hexagonal boron nitride. The oxysilane reacts so that the amino group on the aluminum organic framework reacts with the isocyanate group on 3-isocyanatepropyltriethoxysilane to obtain a functionalized aluminum organic framework, the modified hexagonal boron nitride, the functionalized aluminum organic framework and tetraethyl orthosilicate are hydrolyzed and condensed, and hexadecyltrimethylammonium bromide is used as a template to obtain a composite sol, and the composite sol is treated with tetrabutyl titanate to coat the surface with titanium dioxide sol, and then etched with sodium borohydride, and finally calcined to obtain a modified filler.

[0022] The main molecule of the modified emulsion in the coating solution is polyacrylate, so that the coating solution does not need to add organic solvents, which increases environmental protection. The side chain of the polyacrylate molecule contains a long fluorocarbon chain. Fluorocarbon has a high refractive index and can reduce light reflection, thereby improving light transmittance. At the same time, treatment with sodium borohydride can transform the titanium dioxide sol on the surface into a spike shape. Finally, calcination treatment carbonizes the aluminum organic framework and decomposes hexadecyltrimethylammonium bromide, so that the modified filler forms a porous structure, which cooperates with the spike-shaped titanium dioxide on the surface to form a porous thorn ball. During light irradiation, these incident light rays can be reflected multiple times in the porous thorn-like structure of the modified filler and then consumed and absorbed, thereby reducing the overall reflectivity of the photovoltaic glass. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] A water-based high-transmittance anti-reflection coating solution for photovoltaic glass is prepared by the following steps:

[0026] Step A1: acrylic acid, 2-perfluorooctylethanol, p-toluenesulfonic acid and toluene are uniformly mixed, and reacted at a speed of 120 r / min and a temperature of 110° C. for 5 h to obtain intermediate 1;

[0027] Step A2: Methyl methacrylate, butyl acrylate, acrylic acid, intermediate 1 and deionized water were mixed uniformly, and ammonium persulfate was added under stirring at a speed of 150 r / min and a temperature of 82° C. to react for 2 h to obtain a modified latex;

[0028] Step A3: Weigh the following raw materials in parts by weight: 40 parts of modified emulsion, 5 parts of modified filler, 1 part of sodium dodecylbenzene sulfonate and 20 parts of deionized water, mix the raw materials evenly, and prepare an aqueous high-transmittance anti-reflection coating liquid for photovoltaic glass.

[0029] The molar ratio of acrylic acid to 2-perfluorooctylethanol in step A1 is 1:1, and the amount of p-toluenesulfonic acid used is 1% of the total mass of acrylic acid and 2-perfluorooctylethanol.

[0030] The usage ratio of methyl methacrylate, butyl acrylate, acrylic acid, intermediate 1, deionized water and ammonium persulfate described in step A2 is 95g:73g:54g:35g:150mL:1.58g.

[0031] The modified filler is prepared by the following steps:

[0032] Step B1: Hexagonal boron nitride and sodium hydroxide solution are mixed evenly, ultrasonically treated for 1 hour at a frequency of 30 kHz, heated to 120°C, refluxed for 20 hours, filtered to remove the filtrate, and the substrate is washed with dilute hydrochloric acid until neutral to obtain hydroxylated hexagonal boron nitride. Hydroxylated hexagonal boron nitride, 3-isocyanate propyltriethoxysilane and toluene are mixed, and reacted for 2 hours at a speed of 150 r / min and a temperature of 25°C to obtain modified hexagonal boron nitride;

[0033] Step B2: 2-aminoterephthalic acid, aluminum chloride hexahydrate, DMF and deionized water are mixed, stirred at a speed of 500 r / min and a temperature of 20°C, citric acid is added, stirred for 10 minutes, heated to 150°C, and heat-treated for 20 hours to obtain an aluminum organic framework; the aluminum organic framework, 3-isocyanate propyltriethoxysilane and toluene are mixed, and reacted at a speed of 150 r / min and a temperature of 25°C for 2 hours to obtain a functionalized aluminum organic framework;

[0034] Step B3: uniformly mix the modified hexagonal boron nitride, the functionalized aluminum organic framework, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate and ethanol, perform ultrasonic treatment at a frequency of 20 kHz and a temperature of 40°C, add deionized water, perform ultrasonic treatment for 1 hour, and obtain a composite sol. Disperse the composite sol in ethanol, add tetrabutyl titanate, stir and add deionized water at a speed of 200 r / min and a temperature of 25°C, raise the temperature to 90°C, and react for 1 hour to obtain a modified sol.

[0035] Step B4: Disperse the modified sol in deionized water, add polyvinyl pyrrolidone and sodium borohydride, react at a speed of 150 r / min and a temperature of 60°C for 30 hours, remove the supernatant by centrifugation, repeat step B4 for three times, place the substrate in a muffle furnace, and calcine for 5 hours at a temperature of 550°C in a nitrogen atmosphere to obtain a modified filler.

[0036] The dosage ratio of hexagonal boron nitride and sodium hydroxide solution in step B1 is 1g:100mL, the concentration of sodium hydroxide solution is 5mmol / L, and the dosage of 3-isocyanatepropyltriethoxysilane is 3% of the mass of hydroxylated hexagonal boron nitride.

[0037] The amount ratio of 2-aminoterephthalic acid, aluminum chloride hexahydrate, DMF, deionized water and citric acid in step B2 is 10mmol:10mmol:15mL:6mL:10mmol, and the molar ratio of amino group on the aluminum organic framework and 3-isocyanatepropyltriethoxysilane is 1:1.

[0038] The amount ratio of the modified hexagonal boron nitride, functionalized aluminum organic framework, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, ethanol and deionized water described in step B3 is 1g:1.5g:0.6:2.5g:20mL:3mL, and the amount ratio of the composite sol, ethanol, tetrabutyl titanate and deionized water is 1g:1mL:5μL:9μL.

[0039] The modified sol, deionized water, polyvinyl pyrrolidone and sodium borohydride in step B4 are used in a ratio of 5 g:10 mL:0.15 g:1 mg, and the model of polyvinyl pyrrolidone is K30.

[0040] Example 2

[0041] A water-based high-transmittance anti-reflection coating solution for photovoltaic glass is prepared by the following steps:

[0042] Step A1: acrylic acid, 2-perfluorooctylethanol, p-toluenesulfonic acid and toluene are uniformly mixed, and reacted at a speed of 120 r / min and a temperature of 115° C. for 6 h to obtain intermediate 1;

[0043] Step A2: Methyl methacrylate, butyl acrylate, acrylic acid, intermediate 1 and deionized water were mixed uniformly, and ammonium persulfate was added under stirring at a speed of 150 r / min and a temperature of 83° C., and the mixture was reacted for 3 h to obtain a modified emulsion;

[0044] Step A3: Weigh the following raw materials in parts by weight: 45 parts of modified emulsion, 6 parts of modified filler, 1.5 parts of sodium dodecylbenzene sulfonate and 25 parts of deionized water, mix the raw materials evenly, and prepare an aqueous high-transmittance anti-reflection coating liquid for photovoltaic glass.

[0045] The molar ratio of acrylic acid to 2-perfluorooctylethanol in step A1 is 1:1, and the amount of p-toluenesulfonic acid used is 1% of the total mass of acrylic acid and 2-perfluorooctylethanol.

[0046] The usage ratio of methyl methacrylate, butyl acrylate, acrylic acid, intermediate 1, deionized water and ammonium persulfate described in step A2 is 95g:73g:54g:35g:150mL:1.58g.

[0047] The modified filler is prepared by the following steps:

[0048] Step B1: Hexagonal boron nitride and sodium hydroxide solution are mixed evenly, ultrasonically treated for 1.5 hours at a frequency of 40 kHz, heated to 120°C, refluxed for 20 hours, filtered to remove the filtrate, and the substrate is washed with dilute hydrochloric acid until neutral to obtain hydroxylated hexagonal boron nitride. Hydroxylated hexagonal boron nitride, 3-isocyanate propyltriethoxysilane and toluene are mixed, and reacted at a speed of 200 r / min and a temperature of 25°C for 3 hours to obtain modified hexagonal boron nitride;

[0049] Step B2: 2-aminoterephthalic acid, aluminum chloride hexahydrate, DMF and deionized water are mixed, stirred at a speed of 500 r / min and a temperature of 20°C, citric acid is added, stirred for 15 minutes, heated to 155°C, and heat-treated for 20 hours to obtain an aluminum organic framework, and the aluminum organic framework, 3-isocyanate propyltriethoxysilane and toluene are mixed, and reacted at a speed of 200 r / min and a temperature of 28°C for 2.5 hours to obtain a functionalized aluminum organic framework;

[0050] Step B3: uniformly mix the modified hexagonal boron nitride, the functionalized aluminum organic framework, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate and ethanol, perform ultrasonic treatment at a frequency of 25 kHz and a temperature of 45°C, add deionized water, perform ultrasonic treatment for 1.5 hours, and obtain a composite sol; disperse the composite sol in ethanol, add tetrabutyl titanate, stir and add deionized water at a speed of 200 r / min and a temperature of 30°C, raise the temperature to 93°C, and react for 1.5 hours to obtain a modified sol;

[0051] Step B4: Disperse the modified sol in deionized water, add polyvinyl pyrrolidone and sodium borohydride, react at a speed of 150 r / min and a temperature of 65°C for 33 hours, remove the supernatant by centrifugation, repeat step B4 for three times, place the substrate in a muffle furnace, and calcine for 6 hours at a temperature of 580°C in a nitrogen atmosphere to obtain a modified filler.

[0052] The dosage ratio of hexagonal boron nitride and sodium hydroxide solution in step B1 is 1g:100mL, the concentration of sodium hydroxide solution is 5mmol / L, and the dosage of 3-isocyanatepropyltriethoxysilane is 3% of the mass of hydroxylated hexagonal boron nitride.

[0053] The amount ratio of 2-aminoterephthalic acid, aluminum chloride hexahydrate, DMF, deionized water and citric acid in step B2 is 10mmol:10mmol:15mL:6mL:10mmol, and the molar ratio of amino group on the aluminum organic framework and 3-isocyanatepropyltriethoxysilane is 1:1.

[0054] The amount ratio of the modified hexagonal boron nitride, functionalized aluminum organic framework, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, ethanol and deionized water described in step B3 is 1g:1.5g:0.6:2.5g:20mL:3mL, and the amount ratio of the composite sol, ethanol, tetrabutyl titanate and deionized water is 1g:1mL:5μL:9μL.

[0055] The modified sol, deionized water, polyvinyl pyrrolidone and sodium borohydride in step B4 are used in a ratio of 5 g:10 mL:0.15 g:1 mg, and the model of polyvinyl pyrrolidone is K30.

[0056] Example 3

[0057] A water-based high-transmittance anti-reflection coating solution for photovoltaic glass is prepared by the following steps:

[0058] Step A1: acrylic acid, 2-perfluorooctylethanol, p-toluenesulfonic acid and toluene are uniformly mixed, and reacted at a speed of 150 r / min and a temperature of 120° C. for 7 h to obtain intermediate 1;

[0059] Step A2: Methyl methacrylate, butyl acrylate, acrylic acid, intermediate 1 and deionized water were mixed uniformly, and ammonium persulfate was added under stirring at a speed of 200 r / min and a temperature of 84° C. to react for 3 hours to obtain a modified emulsion;

[0060] Step A3: Weigh the following raw materials in parts by weight: 50 parts of modified emulsion, 8 parts of modified filler, 2 parts of sodium dodecylbenzene sulfonate and 30 parts of deionized water, mix the raw materials evenly, and prepare an aqueous high-transmittance anti-reflection coating liquid for photovoltaic glass.

[0061] The molar ratio of acrylic acid to 2-perfluorooctylethanol in step A1 is 1:1, and the amount of p-toluenesulfonic acid used is 1% of the total mass of acrylic acid and 2-perfluorooctylethanol.

[0062] The usage ratio of methyl methacrylate, butyl acrylate, acrylic acid, intermediate 1, deionized water and ammonium persulfate described in step A2 is 95g:73g:54g:35g:150mL:1.58g.

[0063] The modified filler is prepared by the following steps:

[0064] Step B1: Hexagonal boron nitride and sodium hydroxide solution are mixed evenly, ultrasonically treated for 1.5 hours at a frequency of 50 kHz, heated to 125°C, refluxed for 25 hours, filtered to remove the filtrate, and the substrate is washed with dilute hydrochloric acid until neutral to obtain hydroxylated hexagonal boron nitride. Hydroxylated hexagonal boron nitride, 3-isocyanate propyltriethoxysilane and toluene are mixed, and reacted for 3 hours at a speed of 200 r / min and a temperature of 30°C to obtain modified hexagonal boron nitride;

[0065] Step B2: 2-aminoterephthalic acid, aluminum chloride hexahydrate, DMF and deionized water are mixed, stirred at a speed of 600 r / min and a temperature of 25°C, citric acid is added, stirred for 10-15 minutes, heated to 160°C, and heat-treated for 25 hours to obtain an aluminum organic framework, and the aluminum organic framework, 3-isocyanate propyltriethoxysilane and toluene are mixed, and reacted at a speed of 200 r / min and a temperature of 30°C for 3 hours to obtain a functionalized aluminum organic framework;

[0066] Step B3: The modified hexagonal boron nitride, the functionalized aluminum organic framework, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate and ethanol are uniformly mixed, and deionized water is added under ultrasonic treatment at a frequency of 30 kHz and a temperature of 50°C for 1.5 hours to obtain a composite sol, and the composite sol is dispersed in ethanol, tetrabutyl titanate is added, and deionized water is added under stirring at a speed of 300 r / min and a temperature of 30°C, and the temperature is raised to 95°C for reaction for 1.5 hours to obtain a modified sol;

[0067] Step B4: Disperse the modified sol in deionized water, add polyvinyl pyrrolidone and sodium borohydride, react at a speed of 200 r / min and a temperature of 70°C for 35 hours, remove the supernatant by centrifugation, repeat step B4 for three times on the substrate, place it in a muffle furnace, and calcine it for 7 hours at a temperature of 600°C in a nitrogen atmosphere to obtain a modified filler.

[0068] The dosage ratio of hexagonal boron nitride and sodium hydroxide solution in step B1 is 1g:100mL, the concentration of sodium hydroxide solution is 5mmol / L, and the dosage of 3-isocyanatepropyltriethoxysilane is 3% of the mass of hydroxylated hexagonal boron nitride.

[0069] The amount ratio of 2-aminoterephthalic acid, aluminum chloride hexahydrate, DMF, deionized water and citric acid in step B2 is 10mmol:10mmol:15mL:6mL:10mmol, and the molar ratio of amino group on the aluminum organic framework and 3-isocyanatepropyltriethoxysilane is 1:1.

[0070] The amount ratio of the modified hexagonal boron nitride, functionalized aluminum organic framework, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, ethanol and deionized water described in step B3 is 1g:1.5g:0.6:2.5g:20mL:3mL, and the amount ratio of the composite sol, ethanol, tetrabutyl titanate and deionized water is 1g:1mL:5μL:9μL.

[0071] The modified sol, deionized water, polyvinyl pyrrolidone and sodium borohydride in step B4 are used in a ratio of 5 g:10 mL:0.15 g:1 mg, and the model of polyvinyl pyrrolidone is K30.

[0072] Comparative Example 1

[0073] Compared with Example 1, this comparative example did not add intermediate 1, and the remaining steps were the same.

[0074] Comparative Example 2

[0075] Compared with Example 1, this comparative example does not add modified hexagonal boron nitride, and the remaining steps are the same.

[0076] Comparative Example 3

[0077] Compared with Example 1, the present comparative example did not add the functionalized aluminum organic framework, and the remaining steps were the same.

[0078] Comparative Example 4

[0079] Compared with Example 1, this comparative example did not add hexadecyltrimethylammonium bromide, and the remaining steps were the same.

[0080] Comparative Example 5

[0081] Compared with Example 1, the modified sol in this comparative example is prepared by calcination, and the other steps are the same.

[0082] The coating solutions prepared in Examples 1-3 and Comparative Examples 1-5 were spin-coated onto the glass surface at a speed of 1000 r / min. After curing at room temperature, the transmittance and average reflectivity of the coated glass at 400-780 nm were measured using a UV-visible spectrometer. The test results are shown in the following table.

[0083] ;

[0084] It can be seen from the above table that the present application has good light transmission and anti-reflection effects.

[0085] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. Aqueous high-transmittance anti-reflection coating solution for photovoltaic glass, characterized by: Made by the following steps: Step A1: acrylic acid, 2-perfluorooctylethanol, p-toluenesulfonic acid and toluene are mixed and reacted to prepare intermediate 1; Step A2: methyl methacrylate, butyl acrylate, acrylic acid, intermediate 1 and deionized water are mixed and stirred, and ammonium persulfate is added to react to obtain a modified latex; Step A3: Weigh the following raw materials in parts by weight: 40-50 parts of modified emulsion, 5-8 parts of modified filler, 1-2 parts of sodium dodecylbenzene sulfonate and 20-30 parts of deionized water, and mix the raw materials evenly to prepare a water-based high-transmittance anti-reflection coating solution for photovoltaic glass; The modified filler is prepared by the following steps: Step B1: After mixing hexagonal boron nitride and sodium hydroxide solution for ultrasonic treatment, the mixture is heated to reflux for reaction, the filtrate is filtered to remove the filtrate, the substrate is washed with dilute hydrochloric acid until it is neutral to obtain hydroxylated hexagonal boron nitride, and the hydroxylated hexagonal boron nitride, 3-isocyanate propyltriethoxysilane and toluene are mixed for reaction to obtain modified hexagonal boron nitride; Step B2: 2-aminoterephthalic acid, aluminum chloride hexahydrate, DMF and deionized water are mixed and stirred, and citric acid is added, stirred, and heated to obtain an aluminum organic framework, and the aluminum organic framework, 3-isocyanate propyltriethoxysilane and toluene are mixed and reacted to obtain a functionalized aluminum organic framework; Step B3: Modified hexagonal boron nitride, functionalized aluminum organic framework, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate and ethanol are mixed and ultrasonically treated, and deionized water is added, and the mixture is ultrasonically treated to obtain a composite sol, and the composite sol is dispersed in ethanol, tetrabutyl titanate is added, the mixture is stirred, deionized water is added, and the temperature is raised to react to obtain a modified sol; Step B4: Disperse the modified sol in deionized water, add polyvinyl pyrrolidone and sodium borohydride, react, remove the supernatant by centrifugation, repeat step B4 for three times on the substrate, place it in a muffle furnace, and calcine it to obtain a modified filler.

2. The aqueous high-transmittance anti-reflection coating solution for photovoltaic glass according to claim 1, characterized in that: The molar ratio of acrylic acid to 2-perfluorooctylethanol in step A1 is 1:

1.

3. The aqueous high-transmittance anti-reflection coating solution for photovoltaic glass according to claim 1, characterized in that: The usage ratio of methyl methacrylate, butyl acrylate, acrylic acid, intermediate 1, deionized water and ammonium persulfate described in step A2 is 95g:73g:54g:35g:150mL:1.58g.

4. The aqueous high-transmittance anti-reflection coating solution for photovoltaic glass according to claim 1, characterized in that: The dosage ratio of the hexagonal boron nitride and the sodium hydroxide solution in step B1 is 1 g:100 mL, and the dosage of 3-isocyanatepropyltriethoxysilane is 3% of the mass of the hydroxylated hexagonal boron nitride.

5. The aqueous high-transmittance anti-reflection coating solution for photovoltaic glass according to claim 1, characterized in that: The amount ratio of 2-aminoterephthalic acid, aluminum chloride hexahydrate, DMF, deionized water and citric acid in step B2 is 10mmol:10mmol:15mL:6mL:10mmol, and the molar ratio of amino group on the aluminum organic framework and 3-isocyanatepropyltriethoxysilane is 1:

1.

6. The aqueous high-transmittance anti-reflection coating solution for photovoltaic glass according to claim 1, characterized in that: The amount ratio of the modified sol, deionized water, polyvinyl pyrrolidone and sodium borohydride described in step B4 is 5g:10mL:0.15g:1mg.

Citation Information

Patent Citations

  • Photovoltaic glass with porous-structure and low-refractivity titanium dioxide antireflection coating

    CN103022191A

  • Method for increasing conductivity of metal oxide anode of lithium ion battery

    CN109461913A